Морфологічні особливості плодів і насіння видів родини зонтичних (Umbelliferae Moris. = Apiaceae) - Szikura, A.J.; Szikura, J.J. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2003)
The morphological peculiaritres of fruit, cypsela and seeds of eight genera of Umbelliferae, including species introductive in M.M. Grishko National Botanical Gardens of NAS of Ukraine: Dorema, Eryngium, Ferula, Heracleum, Oedibasis, Prangos, Schrenkia, Seseli, in all 41 species are investigated. With the purpose of deriving botanic of authentic picture we used a photo and computer engineering.